1973
DOI: 10.1021/ja00798a024
|View full text |Cite
|
Sign up to set email alerts
|

Chemical evolution of a nitrogenase model. VI. Reduction of cyanide ion, azide ion, nitrous oxide, molecular nitrogen, and other substrates by molybdocysteine catalysts in the presence of nucleoside phosphates

Abstract: Nitrogenase model systems composed of molybdate and sulfur containing ligands such as l(+> cysteine catalyze the reduction of CN-, N3-, NsO, and N2 with NaBH4 as the reductant. All reactions are stimulated by ATP and other nucleoside phosphates. The reduction of CNyields CH4, NH3, smaller amounts of C2H6, C2H4, and traces of CH3NH2; N3-and N20 are reduced to N2 and NH3 and N2 and H20, respectively, as with nitrogenase. The molybdate-cysteine catalysts also reduce ethylene oxide to C2H4 and H20 and ethyl diazoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1973
1973
1998
1998

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…1-2CN + 6-8e + 6-8H+ --ch4, C2H4, C2H6, NH3(CH3NH2) (2) In the model systems, reduction of CNis very slow in the absence of ATP. Table II shows the effects of ATP and of the five acids on the hydrocarbon product yields at the initial pH of 5.6 (prior to addition of NaBHa).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1-2CN + 6-8e + 6-8H+ --ch4, C2H4, C2H6, NH3(CH3NH2) (2) In the model systems, reduction of CNis very slow in the absence of ATP. Table II shows the effects of ATP and of the five acids on the hydrocarbon product yields at the initial pH of 5.6 (prior to addition of NaBHa).…”
Section: Resultsmentioning
confidence: 98%
“…In the case of ATP, this interaction is accompanied by a molybdenum-catalyzed hydrolysis of ATP to ADP and inorganic phosphate (P¡). 2 The ATP requirement of N2-ase was accordingly interpreted to involve the interaction of ATP with the molybdenum active site, causing the removal of kinetically inert OH group(s) with the simultaneous hydrolysis of ATP into ADP and P¡. The net effect of ATP in N2ase as well as in the model systems was postulated to consist in the acceleration of the conversion of oxidized forms of the molybdenum catalyst into the active reduced form, a process which is slow in the absence of ATP.…”
mentioning
confidence: 99%
“…The authors regard this system as a close model of nitrogenase, although under the optimal conditions the yield of ammonia is extremely small, reaching 0.06-0.1%relative to the initial molybdenum compound after five days at a nitrogen pressure of 140 atm. In later communications 143 ' 144 the authors reported that the results were confirmed with the aid of labelled nitrogen 15 N 2 . Acetylene inhibits the reduction of nitrogen, while carbon monoxide does not affect the yield of ammonia appreciably.…”
Section: The Reduction Of Nitrogen In Molybdenum-thiol Systemsmentioning
confidence: 87%
“…In the first report 141 the authors do not mention iron, while in the next they note that an iron salt is a necessary cocatalyst. Finally, it was stated in a recent communication 144 that an iron salt increases the yield of ammonia only slightly. In the same report 144 , it is unexpectedly stated that the primary reaction product is di-imide, which accumulates in the course of 40 min.…”
Section: The Reduction Of Nitrogen In Molybdenum-thiol Systemsmentioning
confidence: 94%
See 1 more Smart Citation